The Sasak People of Lombok: Indigenous Communities at The Crossroads of Globalization - Ahmad Salehudin (Al-Albab, 2019)
This article focuses on changes that have taken place among Lombok’s indigenous communities, including Sasak Bayan, Sasak Sade, and Sasak Ende. This study found that in the context of thick globalization where information technology is the driving force, the indigenous communities are no longer as the objects of the global cultural market. Instead, they are given the freedom to choose and sort out values that they consider good and appropriate with their needs. In addition, they also exercise the freedom of expression. However, the problem lies in the fact that their choices and ways of expressions are quite often violating old loyalties they have agreed. The communities of Sasak Bayan, Sasak Sade and Sasak Ende provide important information on how indigenous communities respond creatively to globalization based on their needs.